Creatine monohydrate supplementation for older adults and clinical populations - Darren G. Candow; Sergej M. Ostojic; Philip D. Chilibeck; Igor Longobardi; Bruno Gualano; Mark A. Tarnopolsky; Theo Wallimann; Terence Moriarty; Richard B. Kreider; Scott C. Forbes; Uwe Schlattner; Jose Antonio (Journal of the International Society of Sports Nutrition)
Background The biological process of aging is typically associated with a decrease in muscle quantity, muscle performance (primarily strength), bone mass and architecture, functionality and neurological/cognitive function. From a healthy aging perspective, interventions that have the potential to overcome or attenuate these decrements are clinically relevant.Methods We conducted a narrative review on the efficacy of creatine monohydrate supplementation (CrM) in older adults.Results Accumulating research shows that CrM, primarily when combined with exercise training, is safe and has beneficial effects on measures of whole-body lean body mass, regional muscle size, muscle strength, bone area and thickness, functional ability, glucose kinetics, cognition and memory.Conclusion CrM has multiple benefits in older adults and may have application for treating age-related sarcopenia, osteoporosis, frailty, and those with metabolic and neuromuscular disorders.